2023
DOI: 10.1038/s41590-023-01430-3
|View full text |Cite|
|
Sign up to set email alerts
|

CD40 signal rewires fatty acid and glutamine metabolism for stimulating macrophage anti-tumorigenic functions

Abstract: Exposure of lipopolysaccharide triggers macrophage pro-inflammatory polarization accompanied by metabolic reprogramming, characterized by elevated aerobic glycolysis and a broken tricarboxylic acid cycle. However, in contrast to lipopolysaccharide, CD40 signal is able to drive pro-inflammatory and anti-tumorigenic polarization by some yet undefined metabolic programming. Here we show that CD40 activation triggers fatty acid oxidation (FAO) and glutamine metabolism to promote ATP citrate lyase-dependent epigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 43 publications
1
40
0
Order By: Relevance
“…CB839 treatment inhibited this trend, suggesting that GLS plays an essential role in B cell glutaminolysis. The metabolic fate of 13 C-labeled glutamine after R848 treatment confirmed that glutamine was catalyzed into glutamate (M5 labeled) and entered into the tricarboxylic acid (TCA) cycle through α-KG (M5 labeled), succinate (M4 labeled), fumarate (M4 labeled), pyruvate (M3 labeled), and lactate (M3 labeled), which is consistent with the reported glutaminolysis route ( 95 ) (Fig. 6E).…”
Section: Resultssupporting
confidence: 86%
“…CB839 treatment inhibited this trend, suggesting that GLS plays an essential role in B cell glutaminolysis. The metabolic fate of 13 C-labeled glutamine after R848 treatment confirmed that glutamine was catalyzed into glutamate (M5 labeled) and entered into the tricarboxylic acid (TCA) cycle through α-KG (M5 labeled), succinate (M4 labeled), fumarate (M4 labeled), pyruvate (M3 labeled), and lactate (M3 labeled), which is consistent with the reported glutaminolysis route ( 95 ) (Fig. 6E).…”
Section: Resultssupporting
confidence: 86%
“…Subcutaneous tumors demonstrated a pronounced affinity for 18 F‐Gln 104 . Furthermore, research has shown that CD40 activation triggers fatty acid oxidation and glutamine metabolism, promoting the epigenetic reprogramming of pro‐inflammatory genes and the emergence of anti‐tumorigenic phenotypes in macrophages 105 . Compared to glycolysis, the process of the anaplerosis of glutamate plays a crucial role in the survival of tumor cells.…”
Section: Intracellular Metabolism Of Glutamate and Glutaminementioning
confidence: 99%
“…Macrophages respond to tissue damage, inflammation, cellular debris, and metabolic byproducts that are induced by cancer growth. As summarized in Table 1, TAMs play myriad roles in cancer pathogenesis: these include the promotion of inflammation, immunosuppression, 34–36 metabolic support for tumor growth, 37–39 degradation of the extracellular matrix (ECM) through the production of matrix metalloproteases and cathepsins, 40–42 promotion of epithelial–mesenchymal transition (EMT), 43 angiogenesis, 44,45 and metastatic spread 46,47 . The phagocytosis of apoptotic cells and activation of the Tyro3, Axl, and MerTK (abbreviated TAM) receptor tyrosine kinases together is termed efferocytosis; this process leads to the production of anti‐inflammatory signals, immunosuppression, and specific induction of exhaustion in or direct killing of CD8 T cells, 48–51 metabolic competition with immune effector cells and positive feedback loops with cancer‐associated fibroblasts (CAF) and regulatory T cells (Treg) 52–54 …”
Section: Tumor‐infiltrating Myeloid Cellsmentioning
confidence: 99%
“…Activation of CD40 leads to the production of IL‐12 and triggers fatty acid oxidation and glutamine metabolism, thus promoting epigenetic reprogramming to induce pro‐inflammatory gene expression and antitumor responses, particularly when combined with chemotherapy, VEGF blockade, or CSF1R inhibition 91–93 . Metabolic rewiring of TAMs is also seen upon stimulation with CpG (a TLR9 agonist) to overcome the inhibitory “do not eat me” signal 94,95 . TAMs can also be reprogrammed with TREM2 inhibition, 96 using pH‐sensitive nanoparticles to release IL‐12 within the acidic environment, 97 or treatment with small molecule kinase inhibitor; all of these interventions have been shown in preclinical models to result in TME inflammation, promote CD8 T‐cell activation and suppress tumor growth 98 .…”
Section: Manipulating Macrophages For Therapeutic Effect In Cancermentioning
confidence: 99%
See 1 more Smart Citation